ENANTIOSEMY IN THE ANTHROPONYMY OF THE KIPCHAK DIALECT OF SURKHANDARYA REGION (Scientific journal of the Fergana State University, 2026)
This article analyzes the phenomenon of enantiosemy through the example of anthroponyms used in the Kipchak dialect of the Surkhandarya region. The main objective of the study is to identify occurrences of enantiosemy in the local speech system, to reveal their semantic features, and to highlight the linguistic and cultural foundations of this phenomenon. The article reviews existing scholarly sources, examines authentic linguistic material based on methodological approaches, and formulates general conclusions.